Truncation method for countable-point boundary-value problems in the space of bounded number sequences - Nedokis, V. A.; Samoilenko, A. M.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider possible methods for the reduction of a countable-point nonlinear boundary-value problem with nonlinear boundary condition on a segment to a finite-dimensional multipoint problem constructed on the basis of the original problem by the truncation method. The results obtained are illustrated by examples.